2010
DOI: 10.1603/en10156
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Electrophysiological Responses of Tetropium fuscum (Coleoptera: Cerambycidae) to Pheromone and Spruce Volatiles

Abstract: The brown spruce longhorn beetle, Tetropium fuscum (F.), is an invasive wood-boring species in eastern Canada. Gas chromatographic/electroantennographic (GC/EAD) analyses of Norway and red spruce volatiles detected a number of consistent EAD-active responses to compounds that are known to be stress-induced in spruce. The effects of these EAD-active compounds on various aspects of adult behavior were tested. In two-choice olfactometer assays, a monoterpene spruce blend, (R)-(-)-linalool, (3Z,6E)-α-farnesene, (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…A variety of chemical cues is used for host location, such as host kairomones, pheromones of other herbivores (e.g., bark beetles) or smoke volatiles. They usually contain shortchain alpha hydroxyketones or diols, fuscumol ( = geranyl ace tol) in Tetropium and some Lamiinae and possibly Cerambyc inae (Mitchell et al 2011), but occasion ally different compounds and/or more complex blends (e.g., Lacey et al 2008;Ray et al 2009 b); they may also work in synergy with host vola tiles (Ginzel & Hanks 2005;Silk et al 2007Silk et al , 2010. Volatile male produced sex (attracting females) or aggregation (attracting both sexes) pheromones are known in several Cerambyc inae, Lamiinae and Tetropium Kirby of Spondylid inae (Silk et al 2007 for the latter).…”
Section: Cerambycidae Latreille 1802mentioning
confidence: 99%
“…A variety of chemical cues is used for host location, such as host kairomones, pheromones of other herbivores (e.g., bark beetles) or smoke volatiles. They usually contain shortchain alpha hydroxyketones or diols, fuscumol ( = geranyl ace tol) in Tetropium and some Lamiinae and possibly Cerambyc inae (Mitchell et al 2011), but occasion ally different compounds and/or more complex blends (e.g., Lacey et al 2008;Ray et al 2009 b); they may also work in synergy with host vola tiles (Ginzel & Hanks 2005;Silk et al 2007Silk et al , 2010. Volatile male produced sex (attracting females) or aggregation (attracting both sexes) pheromones are known in several Cerambyc inae, Lamiinae and Tetropium Kirby of Spondylid inae (Silk et al 2007 for the latter).…”
Section: Cerambycidae Latreille 1802mentioning
confidence: 99%
“…However, previous studies have shown that high levels of moisture stress, such as those experienced by girdled trees in the present study, can alter the quantity and composition of volatiles emitted by trees (Kimmerer & Kozlowski, 1982;Millar et al, 1986;Ebel et al, 1995), which may influence host selection by Tetropium spp. Tetropium fuscum has also been reported to be attracted to monoterpenes and sesquiterpenes associated with stressed spruce trees (Sweeney et al, 2004;Silk et al, 2010). Tetropium fuscum has also been reported to be attracted to monoterpenes and sesquiterpenes associated with stressed spruce trees (Sweeney et al, 2004;Silk et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Becker, 1962;Broberg & Borden, 2005;Silk et al, 2010) and field trapping experiments (e.g. Becker, 1962;Broberg & Borden, 2005;Silk et al, 2010) and field trapping experiments (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 2,3-butanediol related to fermentation and microbial degradation are highly attractive to P. interrupta, which favors the odors of fermentation products. 72 Other plant volatiles also act synergistically with aggregation pheromones. 59 Allyl isothiocyanate, a specific odor component, is a breakdown product of glucosinolates in oilseed rape, B. napus.…”
Section: Feeding Attractants and Stimulantsmentioning
confidence: 99%